COUNTING MODEL OF BASKETBALL PLAYERS' INJURIES CASE STUDY: NATIONAL BASKETBALL ASSOCIATION (NBA) - BUDI WIBOWO (NIM:10112083), ARIS
In this Final Project, the injury events in the matches experienced by NBA teams during the 2014-15 season are analyzed. The analysis can be used to study the distribution of injury events. By knowing the distribution of injury events, it can be known the probability of injury for the teams observed and a further analysis of the injury events can be carried out. The method used in this Final Project is the Goodness of Fit Test. The Goodness of Fit Test is a method to find out whether a random variable follows a particular distribution or not. The data used are from Pro Sports Transactions Archive (PSTA), Basketball Reference (BR), and NBA Stats. In this Final Project, the teams analyzed are Golden States Warriors, Cleveland Cavaliers, and New York Knicks. This Final Project is expected to be able to describe the injury events in the NBA matches so that a more in-depth analysis can be carried out.